INTERNALISASI NILAI- NILAI MODERASI DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH - Anwar, Ahmad; Almurtaqi, Moch Ridwan (https://www.ejournal.smaamc.sch.id/index.php/belajar, 2024)
This research describes how to internalize the values ​​of religious moderation in Islamic Religious Education learning. The approach used in this research is a qualitative field methodology with analytical descriptive techniques. Data was collected through interviews, observation and documentation, with the respondents being school students. The research results are: Internalization of moderation values ​​is carried out by integrating them into PAI learning, rather than teaching it as a separate subject. Through careful planning, implementation and evaluation, religious moderation is internalized within the school environment, so that students have good morals (akhlak al-karimah) and a comprehensive understanding of their religious meaning. The value of moderation is found in PAI learning through; exploring local wisdom, developing attitudes of tolerance (moderation), interaction in learning, technological innovation in learning, the role of parents and the community.